Model assessments of the Northern Hemisphere continental permafrost changes in the 21st century - M. M. Arzhanov; I. I. Mokhov (Лëд и снег)
Using the results of simulations with an ensemble of Coupled Model Intercomparison Project 6 (CMIP6) models, an analysis of the regimes of the Northern Hemisphere continental permafrost in the 21st century was carried out under various scenarios of anthropogenic forcing. It is noted that the modern boundaries of the permafrost in Northern Eurasia and North America are realistically reproduced using various frost indices based on air temperature and ground temperature. Using various indices, the near-surface permafrost area at the beginning of the 21st century. estimated in the range of 11.5–13.1 million km2. At the same time, the range of the near-surface permafrost area estimates based on simulations with CMIP6 models using the ground temperature is about 11 million km2, which is half as much as similar estimates for the previous generation CMIP5 models. The maximum value of the area trend in the 21st century (–125 thousand km2/year), obtained under the most aggressive scenario ssp5-8.5 is almost twice as large in absolute value as under the least aggressive scenario ssp1.2-6. A decrease in the sensitivity of the permafrost area to changes in global air temperature from the least aggressive to the most aggressive scenario of anthropogenic impacts was revealed: –3.3 million km2/°С under scenario ssp1-2.6, –2.9 million km2/°С under scenario ssp2-4.5 and –2.1 million km2/°С under scenario ssp5-8.5. Analysis of the results showed that with an increase in the rate of global warming for the most aggressive anthropogenic scenarios, a significant increase in temperature in high latitudes leads to rapid degradation of the permafrost in the second half of the 21st century in the north of Eurasia, and according to certain models in Tibet and North America with the exception Canadian Arctic.